2016
DOI: 10.1007/s10897-016-0041-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Living with Klinefelter Syndrome: A Qualitative Exploration of Adolescents and Adults

Abstract: Klinefelter syndrome (XXY) is a common yet significantly underdiagnosed condition with considerable medical, psychological and social implications. Many health care providers lack familiarity with XXY, resulting in medical management challenges and a limited understanding of the personal impact of the condition. Genetic counselors benefit from understanding the challenges adolescents and men with XXY face to effectively address their medical and psychosocial needs. The purpose of this study was to understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 39 publications
6
41
0
1
Order By: Relevance
“…The disclosure of KS diagnosis to these children can be challenging for their parents and physicians (Girardin and Van Vliet 2011;Dennis et al 2015). Few studies have focused on how to disclose a KS diagnosis to this group, and there is no consensus on guidelines for diagnosis disclosure (Stochholm et al 2006;Dennis et al 2015;Tremblay et al 2016;Turriff et al 2017). It has been suggested that healthcare professionals (HCPs) partner with parents to disclose KS diagnosis to their child (Tremblay et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The disclosure of KS diagnosis to these children can be challenging for their parents and physicians (Girardin and Van Vliet 2011;Dennis et al 2015). Few studies have focused on how to disclose a KS diagnosis to this group, and there is no consensus on guidelines for diagnosis disclosure (Stochholm et al 2006;Dennis et al 2015;Tremblay et al 2016;Turriff et al 2017). It has been suggested that healthcare professionals (HCPs) partner with parents to disclose KS diagnosis to their child (Tremblay et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognized that a prenatal diagnosis affects parental perception and expectations for their child. It is also understood that the type of medical professional providing the post‐result counseling, as well as the type of scientific literature presented, can significantly impact whether a termination takes place, and the parent's expectation as their child develops . This altered perception can be optimized if prenatal counseling is sensitive and comprehensive in providing current information on the neuropsychology, fertility, and neurodevelopmental progression associated with this disorder.…”
Section: Future Considerationsmentioning
confidence: 99%
“…57 Health care providers doing the counseling need to have a current understanding of the disorder as well as its longitudinal impact on quality of life. 57…”
Section: Limitations Of Noninvasive Prenatal Testingmentioning
confidence: 99%
See 2 more Smart Citations